Pendampingan Pembelajaran Kajian Fikih Kitab Bulughul Maram di Bulan Ramadhan - Ulum, Miftachul; Mun’im, Abdul; Zawawi , Abdullah (Rahmah : Jurnal Pengabdian Masyarakat, 2025)
The community mentoring activity aims to equip participants, especially students, with a comprehensive understanding of the legal hadiths which are the main basis for daily religious practice. The implementation method is with bandongan, namely the mentor reads the text of the Bulughul Maram book accompanied by an explanation of the hadith lafaz, syarah (explanation of meaning), and the legal context contained therein. The results of the mentoring activity for the study of the Bulughul Maram book show several significant achievements, both from the cognitive, affective, and psychomotor aspects of the participants. There was an increase in the participants' understanding of the concept of thaharah and the practice of purification, which was reflected. Strengthening the Scientific Tradition Participants showed high enthusiasm in participating in studies and discussions, which indicates the development of a spirit of learning and scientific traditions in the Islamic boarding school environment